2019
DOI: 10.1152/ajpcell.00205.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and inflammatory mediator effects on TRPV4 function in choroid plexus epithelial cells

Abstract: The choroid plexus (CP), composed of capillaries surrounded by a barrier epithelium, is the main producer of cerebrospinal fluid (CSF). The CP epithelium regulates the transport of ions and water between the blood and the ventricles, contributing to CSF production and composition. Several studies suggest a connection between the cation channel transient receptor potential vanilloid-4 (TRPV4) and transepithelial ion movement. TRPV4 is a nonselective, calcium-permeable cation channel present in CP epithelia repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 54 publications
3
23
0
Order By: Relevance
“…In the Tmem67 -/genetic model of communicating hydrocephalus, we have shown that 2 different TRPV4 antagonists inhibit the development of ventriculomegaly. These data are in agreement with in vitro studies in cultured CP epithelia demonstrating that TRPV4 agonists stimulate a multiphasic transepithelial ion flux that can be inhibited by either of the 2 antagonists used in the current study (10)(11)(12). The mechanism of action and the role of TRPV4 in the development of hydrocephalus do not appear to be dependent on increased expression of the channel protein, suggesting that the mechanism is, rather, a change in cell surface expression and/or activation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the Tmem67 -/genetic model of communicating hydrocephalus, we have shown that 2 different TRPV4 antagonists inhibit the development of ventriculomegaly. These data are in agreement with in vitro studies in cultured CP epithelia demonstrating that TRPV4 agonists stimulate a multiphasic transepithelial ion flux that can be inhibited by either of the 2 antagonists used in the current study (10)(11)(12). The mechanism of action and the role of TRPV4 in the development of hydrocephalus do not appear to be dependent on increased expression of the channel protein, suggesting that the mechanism is, rather, a change in cell surface expression and/or activation.…”
Section: Discussionsupporting
confidence: 90%
“…However, the nonselective nature of the channel allows for the transport of other cations, notably Na + (22). The changes in intracellular ion concentrations secondarily alter other channels and transporters leading to the transepithelial flux of both electrolytes and water (10,11,23). Figure 8A shows the effect of TRPV4 activation on the influx of Ca 2+ in freshly isolated CP from the rat model.…”
Section: Figure 2 Amelioration Of Cranial Doming By P15 In Hydrocephmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, inflammatory cytokines abolished this effect and led to a downregulation of Trpv4 in MbMECs. Consistently, previous data showed that proinflammatory cytokines (e.g., TNF-α and IL-1β) had inhibitory effects on TRPV4-stimulated transepithelial ion flux and permeability changes in the choroid plexus, whereas antiinflammatory cytokines (e.g., IL-10 and IL-4) showed no effect (Simpson et al, 2019). However, in this study the cytokines reduced only the functional but not the transcriptional regulation of TRPV4.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence suggests that inflammatory pathways at the choroid plexus regulate CSF secretion. Interestingly, Simpson et al [73] showed that cytokines and other inflammatory mediators regulate a non-selective cation channel, transient receptor potential vanilloid-4 (TRPV4), at the epithelium. There is some controversy about the role of the apically located Na + /K + /Cl −cotransporter (NKCC1) at the choroid plexus epithelium.…”
Section: Choroid Plexusmentioning
confidence: 99%